2010
DOI: 10.2527/jas.2010-2972
|View full text |Cite
|
Sign up to set email alerts
|

Differential composition of proteomes in sow colostrum and milk from anterior and posterior mammary glands1

Abstract: Piglets obtaining milk from anterior and middle mammary glands (MG) grow faster than those suckling posterior MG, but the underlying mechanisms are not clear. The purpose of this study was to investigate the differential proteomes of colostrum and milk secreted by anterior and posterior MG. Six healthy primiparous sows with 7 pairs of MG were used; the first and the second pairs were defined as anterior MG and the sixth and seventh pairs as posterior MG. Colostrum and milk were collected at d 1 and 14 after pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 59 publications
3
50
0
6
Order By: Relevance
“…Offspring that obtain milk from anterior and middle mammary glands (MGs) grow faster than those suckling posterior MG (Puppe and Tuchscherer, 1999;Kim et al, 2000). Besides the greater amount of colostrum and milk from anterior and middle MGs (Gill and Thomson, 1956), we reported that components in colostrum and milk secreted by anterior and posterior MGs are also distinctive (Wu W.Z. et al, 2010) in having proteins that are beneficial to passive immunity, intestinal development, and epithelial integrity; they include immunoglobulins and haptoglobin in colostrum and lactoferrin in milk from anterior MG, which are more abundant in anterior and middle MGs compared with posterior MG.…”
Section: Pre-weaning Growth Performancementioning
confidence: 87%
“…Offspring that obtain milk from anterior and middle mammary glands (MGs) grow faster than those suckling posterior MG (Puppe and Tuchscherer, 1999;Kim et al, 2000). Besides the greater amount of colostrum and milk from anterior and middle MGs (Gill and Thomson, 1956), we reported that components in colostrum and milk secreted by anterior and posterior MGs are also distinctive (Wu W.Z. et al, 2010) in having proteins that are beneficial to passive immunity, intestinal development, and epithelial integrity; they include immunoglobulins and haptoglobin in colostrum and lactoferrin in milk from anterior MG, which are more abundant in anterior and middle MGs compared with posterior MG.…”
Section: Pre-weaning Growth Performancementioning
confidence: 87%
“…Após o nascimento, os leitões são direcionados a mamar o colostro, rico em imunoglobulinas e importante para sua imunidade passiva e desenvolvimento intestinal (23) . Durante este período, os leitões são expostos ao aparelho mamário da porca e, nas primeiras dezoito horas, elegem um teto preferencial, sendo que neste período ocorrem disputas entre indivíduos e cada lactente poderá mamar em três ou quatro tetos diferentes (24,25) .…”
Section: Resultados E Discussõesunclassified
“…Par contre, l'effet de la parité sur la concentration colostrale d'Igs est remarquable chez la truie avec une plus forte concentration d'IgG et d'IgA dans le colostrum des multipares (à partir de parité 4) (Quesnel, 2011b ;CarneyHinkle et al, 2013). L'effet de la position des tétines sur la qualité du colostrum a été aussi observé, le colostrum des mamelles antérieures étant plus riche en Igs que celui des postérieures (Wu et al, 2010).…”
Section: Transfert Des Cellules Et Des Facteurs Antimicrobiens Aux Pounclassified